Polycentric Model of Development of Partner Relations as an Instrument of Development of the Russian Federation’s Regions - Vyacheslavovna Kadatskaya, Daria; Ivanovich Seliverstov, Yury; Aleksandrovna Nikitina, Elena; Petrovna Gavrilovskaya, Svetlana; ., . (International Journal of Engineering and Technology, 2018)
The search for new drivers for the development of the Russian Federationâ€™s regions from the point of view of innovative transformations is currently relevant. In the current economic conditions, the role of the higher school in the training of demanded personnel is growing. Today, the university can and should become a reliable integrator of the business environment with state and municipal authorities. For the consortium of business environment, state authorities and universities, today there are significant barriers due to lack of infrastructure, good legal support, transparency of communication, sources of financing, etc. In order to optimize this process, the paper proposes the AUB polycentric partnership model, which will ensure free entry to and exit from the consortium, attracting the maximum number of participants, taking into account the elimination of possible risks.Â Â